In Vivo pharmacokinetic interactions of ribociclib with rivaroxaban and apixaban in rats: implications for increased drug exposure and dose adjustments - Liu, Zihan; Du, Wenyu; Wang, Qimin; Wang, Zhi; An, Jing; Ma, Yinling; Dong, Zhanjun; Li, Ying (Frontiers in Pharmacology, 2025)
BackgroundApixaban (API) and rivaroxaban (RIVA) are orally available inhibitors of coagulation factor Xa and are commonly used to treat cancer-related venous thrombosis. Ribociclib (RIBO), a first-line treatment for hormone receptor-positive/human epidermal growth factor receptor 2 negative (HR+/HER2−) advanced breast cancer, is an inhibitor of CYP3A4, P-gp, and BCRP. Given the potential for these drugs to be co-administered in clinical settings, there is limited information regarding the pharmacokinetic drug-drug interactions (DDIs) between ribociclib and these anticoagulants. This study aimed to evaluate the extent of DDIs between ribociclib and rivaroxaban or apixaban in rats and to explore the optimization of drug dosing strategies.MethodsMale Sprague-Dawley rats were divided into 9 groups (n = 6), receiving ribociclib, apixaban, rivaroxaban, ribociclib with rivaroxaban, ribociclib with apixaban, and combinations with reduced doses and time intervals. Blood concentrations were measured using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Pharmacokinetic parameters such as AUC, Cmax, CLz/F, and Vz/F.ResultsRibociclib significantly increased exposure to both rivaroxaban and apixaban, with a greater impact on rivaroxaban. Specifically, ribociclib increased the AUC0-t, AUC0-∞ and Cmax of rivaroxaban (normal dose) by about 2.4-fold, 2.1-fold and 1.8-fold, while increasing apixaban exposure by about 60.82%, with a trend towards an increase in Cmax that was not statistically significant. When co-administered with ribociclib, even at a reduced dosage of 1 mg/kg, rivaroxaban exhibited a significant increase in exposure, with the AUC increasing by 2.3-fold and Cmax by 1.3-fold. Despite the reduction in dosage, the pharmacokinetic effect of ribociclib on rivaroxaban persisted. While administration of rivaroxaban 12 h after ribociclib resulted in a less pronounced increase in exposure compared to the normal-dose group. The results of qRT-PCR showed that ribociclib reduced the expression of Cyp3a1 and Abcg2 in rat intestine.DiscussionThis research highlights the need for careful consideration of dosing regimens to minimize toxicity risk and optimize the safety of clinical co-administration of ribociclib with rivaroxaban.